SOME PROPERTIES OF INTUITIONISTIC FUZZY BI-IDEALS OF NEAR RINGS - KUMAR*, K. DHILIP; RAMACHANDRAN, M. (International Journal of Mathematical Archive, 2018)
In this present paper, we introduce the concept of intuitionistic fuzzy bi-ideals of near-rings. Also we investigate some algebraic nature of intuitionistic fuzzy bi-ideals of near-rings and some related properties of these fuzzy substructures.